Evaluasi Evaluasi Material Waterway Terhadap Optimalisasi Daya PLTM Sion 2 X 5 MW - Asih Ratnasari; Maria Angela Kartawidjaja (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2025)
Mini-Hydro Power Plants (PLTM) are a renewable energy source with significant potential in Indonesia, yet their utilization remains under-utilized. This study aims to evaluate the effect of waterway materials on power efficiency at the Sion PLTM in North Sumatra. The goal is to optimize power efficiency by selecting waterway materials, as well as to provide knowledge and a template for future similar projects or studies. The evaluation was conducted by comparing three types of channel materials: Open Channel (open concrete channel), Glass Fiber Reinforced Plastic (GRP) pipe, and High-density Polyethylene (HDPE) pipe. This study measured and compared the head loss, power output, and power efficiency of each material. The calculations revealed the lowest head loss value for GRP pipe (1.17 m), followed by HDE pipe (2.34 m), and Open Channel (18.14 m). Meanwhile, the results of the comparison of the power produced, the highest power was obtained from GRP pipes (13,624.64 kW), followed by HDPE pipes (13,406.21 kW) and Open Channel (10,456.51 kW). In conclusion, GRP pipe material is the most optimal choice for improving power efficiency at PLTM Sion, supporting the enhanced utilization of renewable energy to replace fossil fuels.